Effectiveness of endothelial cell seeding on patency of damaged vascular surfaces in a canine model - Darçin, OT; Islamoglu, F; Yagdi, T; Boga, M; Doymaz, MZ; Gezen, MR (Springer-Verlag, 2001)
The effects of endothelial cell seeding, which is assumed to be an effective technique to improve patency rates of denuded vascular surfaces, were investigated in an experimental model. In this study, after anesthetic induction, jugular veins of 16 dogs were harvested bilaterally. Endothelial cells were extracted enzymatically by collagenase from these veins and were passaged into a culture medium until they grew to a reasonable number. After 3 weeks, dogs were anesthetized again in a similar fashion and bilateral femoral veins were exposed and experimental intimal denudation was performed. Subsequently, one femoral artery was injected with cell solution and the other with saline solution as a control. Two weeks after the injections, arteriographic studies of femoral arteries were performed and arterial specimens were taken for histological evaluation. Our results suggest that endothelial seeding might improve the patency rate in elective but urgent cases in which endarterectomy, percutaneous transluminal angioplasty, or similar vascular procedures are considered.
Keywords: Superficial Femoral-Artery; Carotid Endarterectomy; Occlusive Disease; Angioplasty; Atherectomy